Swept-Source OCT Angiography of the Retinal Vasculature Using Intensity Differentiation-based Optical Microangiography Algorithms - Huang, Yanping; Zhang, Qinqin; Thorell, Mariana R.; An, Lin; Durbin, Mary K.; Laron, Michal; Sharma, Utkarsh; Gregori, Giovanni; Rosenfeld, Philip J.; Wang, Ruikang K. (Ophthalmic surgery, lasers & imaging, 2014)
To demonstrate the feasibility of using a 1,050-nm swept-source optical coherence tomography (SS-OCT) system to achieve noninvasive retinal vasculature imaging in human eyes. Volumetric data sets were acquired using a 1-µm SS-OCT prototype that operated at a 100-kHz A-line rate. A scanning protocol designed to allow for motion contrast processing, referred to as OCT angiography or optical microangiography (OMAG), was used to scan an approximately 3 × 3–mm area in the central macular region of the retina within approximately 4.5 seconds. An intensity differentiation-based OMAG algorithm was used to extract three-dimensional retinal functional microvasculature information. Intensity signal differentiation generated capillary-level resolution en face OMAG images of the retina. The parafoveal capillaries were clearly visible, thereby allowing visualization of the foveal avascular zone in healthy subjects. The capability of OMAG to produce retinal vascular images was demonstrated using the 1-µm SS-OCT prototype. This technique has potential clinical value for studying retinal vasculature abnormalities.